The POTENTIAL OF RATUN ORGANS OF FERMENTED SORGUM (Sorghum bicolor L.) PRODUCED IN SWAMP AS BIOHERBICIDE - Edi Susilo; Pujiwati, Hesti (BPFP Universitas Bengkulu, 2022)
[POTENTIAL OF FERMENTED RATOON ORGANS OF SORGUM (Sorghum bicolor L.) CULTIVATED IN SWAMP LAND AS BIOHERBICIDE]. Sorghum is one of the allelopathy-producing plants and the allelochemical content of sorghum plant parts varies. Therefore, each ratoon organs of sorghum has the potential as a bioherbicide. The aim of this study was to determine the potential of water extracts of six months-fermented ratoon sorghum organs cultivated in swamp lands as bioherbicides. The research was conducted in swamp land in Kandang Limun and Bentiring Permai Bengkulu City, Bengkulu Province from November 2020 to May 2021 and continued until October 2022 for bioassay experiment. The experimental design was a Completely Randomized Design (CRD) with a single factor with four replications. The treatment was fermented ratoon sorghum water extract for six months consisting of four levels (i.e., control, leaf, stem and root). Twenty five of mung bean seeds Vima 1 variety was planted in a petri dish containing 10 mL of fermented ratoon organs and incubated for three days. The results showed that water extract of fermented ratoon plants was able to inhibit sorghum seed germination. Water extracts of fermented sorghum stems and roots was more potential as a source of bioherbicides than those of sorghum leaves or controls. Therefore, it is recommended to use the ratoon sorghum roots or stems for bioherbicide.